Timeliness of Diagnosing Lung Cancer. Issue 29 (July 2015) - Verma, Akash; Lim, Albert Y.H.; Tai, Dessmon Y.H.; Goh, Soon Keng; Kor, Ai Ching; A., Dokeu Basheer A.; Chopra, Akhil; Abisheganaden, John; Levent, Dalar.
<x xml:space="preserve">Abstract</x> Abstract To study number of procedures and time to diagnose lung cancer and factors affecting the timeliness of clinching this diagnosis. Retrospective cohort study of lung cancer patients who consecutively underwent diagnostic bronchoscopy in 1 year (October 2013 to September 2014). Out of 101 patients diagnosed with lung cancer from bronchoscopy, average time interval between first abnormal computed tomogram (CT) scan-to-1st procedure, 1st procedure-to-diagnosis, and 1st abnormal CT scan-to-diagnosis was 16 ± 26, 11 ± 19, and 27 ± 33 days, respectively. These intervals were significantly longer in those requiring repeat procedures. Multivariate analysis revealed inconclusive 1st procedure to be the predictor of prolonged (>30 days) CT scan to diagnosis time (P = 0.04). Twenty-nine patients (28.7%) required repeat procedures (n = 63). Reasons behind repeating the procedures were inadequate procedure (n = 14), inaccessibility of lesion (n = 9), inappropriate procedure (n = 5), mutation analysis (n = 2), and others (n = 2). Fifty had visible endo-bronchial lesion, 20 had positive bronchus sign, and 83 had enlarged mediastinal/hilar lymph-nodes or central masses adjacent to the airways. Fewer procedures, and shorter procedure to diagnosis time, were observed in those undergoing convex probe endobronchial ultrasound-transbronchial needle aspiration (EBUS-TBNA) (P = 0.04). Most patients exhibit enlarged mediastinal lymph node or mass adjacent to the central airway accessible by convex probe EBUS-TBNA. Hence, combining it with conventional bronchoscopic techniques such as bronchoalveolar lavage, brush, and forceps biopsy increases detection rate, and reduces number of procedures and time to establish diagnosis. This may translate into cost and resource savings, timeliness of diagnosis, greater patient satisfaction, and conceivably better outcomes.